Solving Generalized Wave and Heat Equations Using Linear Canonical Transform and Sampling Formulae - Mawardi Bahri; Ryuichi Ashino (Abstract and Applied Analysis)
Several essential properties of the linear canonical transform (LCT) are provided. Some results related to the sampling theorem in the LCT domain are investigated. Generalized wave and heat equations on the real line are introduced, and their solutions are constructed using the sampling formulae. Some examples are presented to illustrate our results.